Sex Differences in Civilian Injury in Baghdad From 2003 to 2014: Results of a Randomized Household Cluster Survey. Issue 6 (June 2018) - Shaak, Kyle; Lafta, Riyadh; Stewart, Barclay T.; Fowler, Thomas R.; Al-Shatari, Sahar A. Esa; Burnham, Gilbert; Cherewick, Megan; Wren, Sherry M.; Groen, Reinou S.; Kushner, Adam L.
Abstract : Objective: To examine sex differences in injury mechanisms, injury-related death, injury-related disability, and associated financial consequences in Baghdad since the 2003 invasion of Iraq to inform prevention initiatives, health policy, and relief planning. Background: Reliable estimates of injury burden among civilians during conflict are lacking, particularly among vulnerable subpopulations, such as women. Methods: A 2-stage, cluster randomized, community-based household survey was conducted in May 2014 to determine the civilian burden of injury in Baghdad since 2003. Households were surveyed regarding injury mechanisms, healthcare required, disability, deaths, connection to conflict, and resultant financial hardship. Results: We surveyed 900 households (5148 individuals), reporting 553 injuries, 162 (29%) of which were injuries among women. The mean age of injury was higher among women compared with men (34 ± 21.3 vs 27 ± 16.5 years; P < 0.001). More women than men were injured while in the home [104 (64%) vs 82 (21%); P < 0.001]. Fewer women than men died from injuries [11 (6.8%) vs 77 (20%); P < 0.001]; however, women were more likely than men to live with reduced function [101 (63%) vs 192 (49%); P = 0.005]. Of intentional injuries, women had higher rates of injury by shell fragments (41% vs 26%); more men were injured by gunshots [76 (41%) vs 6 (17.6%); P = .011). Conclusions: Women experienced fewer injuries than men in postinvasion Baghdad, but were more likely to suffer disability after injury. Efforts to improve conditions for injured women should focus on mitigating financial and provisional hardships, providing counseling services, and ensuring access to rehabilitation services.